Estrategias lúdicas y logros de aprendizaje del área de desarrollo personal, ciudadanía y cívica en estudiantes de secundaria en comunidades del Río Napo 2023 - Salazar Sosa, Nancy Paola (2024)
In this research, the main objective was to determine the relationship between the level of development of recreational strategies and learning in Personal Development, Citizenship and Civics of high school students in communities of the Napo River during the year 2023. The approach of the work was correlational, opting for a quantitative design to collect data. The study population included 130 high school students in the Napo River communities in 2023, and census sampling was used, considering the entire population as the sample. To collect information about recreational strategies and learning in the aforementioned area, the questionnaire was used as an evaluation instrument. The most notable results revealed that, with an error level of 0.0%, there is a very strong correlation between the level of application of playful strategies and academic performance. Consequently, the research hypothesis was confirmed, indicating that there is a significant relationship between the level of implementation of recreational strategies and learning achievement in Personal Development, Citizenship and Civics in high school students from the Napo River communities in 2023.